Bimodal polyethylene copolymer and films thereof

CN115884993BActive Publication Date: 2026-10-09DOW GLOBAL TECHNOLOGIES LLC
View PDF 47 Cites 0 Cited by

Patent Information

Application Number
CN202180051067.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-22
Filing Date
2021-09-20
Publication Date
2026-10-09
Estimated Expiration
2041-09-20

Smart Images

  • Figure BDA0004084957120000231
    Figure BDA0004084957120000231
  • Figure BDA0004084957120000241
    Figure BDA0004084957120000241
  • Figure BDA0004084957120000242
    Figure BDA0004084957120000242
Patent Text Reader

Abstract

A bimodal copolymer comprising an average of at least 90 wt% of units derived from ethylene and at least 0.05 wt% of units derived from an alpha-olefin comonomer having from 4 to 10 carbon atoms, wherein the copolymer has the properties described herein.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to polyethylene copolymers, polymer formulations, films, articles, and related methods.

[0002] Explanation of related fields

[0003] The preparation of polyethylene copolymers with bimodal molecular weight distributions is known; these polyethylene copolymers are referred to as "bimodal polyethylene copolymers". Bimodal polyethylene copolymers can be produced in two or more reactors or in a single reactor using a bimodal catalyst system. Patent applications relating to bimodal polyethylene copolymers and their production include US2007 / 0043177 A1; US ​​2009 / 0036610 A1; US ​​2020 / 0071509 A1, WO 2009 / 148487 A1, WO2019 / 241045 A1, WO 2020 / 046663 A1, and WO 2020 / 068413 A1. Patents relating to bimodal polyethylene copolymers and their production include US 5.539,076; US 5,882,750; US 6,403,181 B1; US ​​7,090,927; US 8,110,644 B2 and US 8,378,029 B2.

[0004] It is also known to produce polyethylene copolymer films, such as by cast film extrusion or blown film extrusion. See, for example, LyondellBasell, A Guide to Polyolefin Film Extrusion, Publication 6047 / 1004 (available at lyb.com) and Qenos Pty, Ltd., Film Extrusion and Conversion-Technical Guide (July 2015) (available at qenos.com). Summary of the Invention

[0005] One aspect of the invention is a bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0006] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0007] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0008] (c) The weight-average molecular weight (M) of the higher molecular weight fraction w ) is the weight-average molecular weight (M) of the lower molecular weight fraction. w 30 to 50 times that of ).

[0009] (d) The total melt flow ratio of the copolymer (I) 21 / I2) is at least 90; and

[0010] (e) The total Mz / Mw ratio of the copolymer is at least 8; and

[0011] (f) The oligomer content of the copolymer does not exceed 1000 ppm, as measured by the gas chromatography method described herein;

[0012] A second aspect of the invention is a bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0013] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0014] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0015] (c) The total melt flow ratio (I) of the copolymer 21 / I2) is at least 90; and

[0016] (d) The total melt flow ratio of the copolymer (I) 21 / I5) is 22 to 35; and

[0017] (e) The total Mz / Mw ratio of the copolymer is at least 8; and

[0018] (f) The oligomer content of the copolymer does not exceed 1000 ppm, as measured by the gas chromatography method described herein.

[0019] A third aspect of the invention is a bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0020] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0021] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0022] (c) The total melt flow ratio (I) of the copolymer 21 / I2) is at least 90; and

[0023] (d) The total Mz / Mw ratio of the copolymer is at least 8; and

[0024] (e) As measured by the gas chromatography method described herein, the oligomer content of the copolymer does not exceed 1000 ppm; and

[0025] (f) The PENT value (2.4 MPa and 80 °C) of the copolymer is at least 600 (600.0) hours.

[0026] A fourth aspect of the invention is a bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0027] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0028] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0029] (c) The total melt flow ratio (I) of the copolymer 21 / I2) is at least 90; and

[0030] (d) The total Mz / Mw ratio of the copolymer is at least 8; and

[0031] (e) As measured by the gas chromatography method described herein, the oligomer content of the copolymer does not exceed 1000 ppm; and

[0032] (f) The copolymer is produced by polymerizing the ethylene monomer and the α-olefin comonomer in the presence of a bimodal catalyst comprising both of the following:

[0033] (i) (cyclopentadienyl)(1,5-dimethylindenyl)zirconium (X)2 components, wherein X is the part that realizes the valence of the zirconium; and

[0034] (ii) Bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium component.

[0035] A fifth aspect of the invention is a bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0036] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0037] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0038] (c) The total melt flow ratio (I) of the copolymer 21 / I2) is at least 90; and

[0039] (d) The total Mz / Mw ratio of the copolymer is at least 8; and

[0040] (e) As measured by the gas chromatography method described herein, the oligomer content of the copolymer does not exceed 1000 ppm; and

[0041] (f) The copolymer also contains at least 20 ppb of one or more dimethyl-1H-indenyl compounds.

[0042] A sixth aspect of the invention is a membrane comprising any of these bimodal copolymers.

[0043] A seventh aspect of the present invention is a method for preparing a blown film, the method comprising: melting any of the bimodal copolymers to obtain a melt thereon; extruding the melt through a mold configured to form bubbles to prepare bubbles of the bimodal copolymer; and blowing (inflating) the bubbles with a blown film machine to prepare the blown film. Detailed Implementation

[0044] The invention summary and abstract are incorporated herein by reference.

[0045] definition

[0046] The following definitions are used in this specification:

[0047] Activator. A substance other than either a catalyst or a matrix that increases the rate of a catalytic reaction without being consumed itself. Typically, the activator contains aluminum and / or boron.

[0048] bimodal copolymer This refers to an ethylene copolymer composition containing both a higher molecular weight (HMW) copolymer component and a lower molecular weight (LMW) copolymer component. The relative terms "higher" and "lower" in HMW and LMW are used interchangeably and refer only to the weight-average molecular weight (Mb) of the HMW component. w-HMW The weight-average molecular weight (M) of the LMW component is greater than that of the LMW component. w-LMW ), that is, M w-HMW >M w-LMW The bimodal copolymer is characterized by two peaks separated by distinguishable local minima in a graph of dW / dLog(MW) on the y-axis versus Log(MW) on the x-axis, used to give a gel permeation chromatography (GPC) chromatogram, wherein Log(MW) and dW / dLog(MW) are as defined herein and measured by the gel permeation chromatography (GPC) test method described herein.

[0049] Bimodal catalystThis refers to a catalyst system containing two different catalysts used to catalyze the polymerization of ethylene copolymers and produce bimodal copolymer compositions. The two catalysts typically differ from each other in at least one of the following properties: (a) their catalytic metals are different (e.g., Ti vs. Zr, Zr vs. Hf, Ti vs. Hf; non-activating metals such as Al); (b) one catalyst has a functional ligand bonded to its catalytic metal, while the other catalyst does not; (c) both catalysts have functional ligands bonded to their catalytic metals, and the structure of at least one functional ligand of one catalyst differs from the structure of a functional ligand of the other catalyst; and (d) for catalysts disposed on support materials, the compositions of these support materials are different. The two catalysts in a bimodal catalyst system can be disposed on the same support material, on the same particles of the same support material, or each on different particles of the same support material. When the catalyst system contains the same catalyst with respect to the catalytic metal and ligands, wherein a portion of it is disposed on the support material and its different portions are dissolved in an inert solvent, these different portions do not themselves constitute a bimodal catalyst system.

[0050] catalyst. Materials that initiate and / or increase the polymerization rate of ethylene and α-olefin comonomers.

[0051] Catalyst system. The catalyst itself and the combination of accompanying materials, such as activators or other modifier compounds used to change the reactivity of the catalyst, a support material on which the catalyst is disposed, a carrier material in which the catalyst is disposed, or any two or more of these combinations.

[0052] dry. Typically, the moisture content is 0 to less than 5 parts per million on a total weight basis. The material fed into the reactor during the polymerization reaction is dry.

[0053] Ethylene. Polymerizable monomers of the formula H2C=CH2.

[0054] Feeding. The amount of reactants or reagents added or “feeded” into the reactor. In continuous polymerization operations, each feed can be independent, either continuous or intermittent. The amount or “feed” can be measured, for example, by metering, to control the quantity and relative amount of various reactants and reagents in the reactor at any given time.

[0055] Feed pipeline. Pipe or conduit structure used for conveying feed materials.

[0056] membrane:A one-dimensional article. The restricted dimension may be referred to as film thickness, and the thickness (gauge variation) therein is substantially uniform.

[0057] 1-Hexene. The polymerizable monomer of the formula H2C=C(H)CH2CH2CH2CH3.

[0058] Inertia. Typically, the polymerization reaction in this invention does not react significantly or cause significant interference. The term "inert" applied to the purge gas or ethylene feed means a molecular oxygen (O2) content of 0 to less than 5 parts per million based on the total weight of the purge gas or ethylene feed.

[0059] Internal bubble cooling or IBC This is the aspect of membrane blow molding performed by actively using auxiliary dedicated IBC equipment (such as the IBC equipment of RECree. US 2002 / 0150648 A1).

[0060] straight-chain α-olefins The formula is H₂C = C(H)(CH₂). r A polymerizable monomer of CH3, where r is a number from 0 to 7.

[0061] Metallocene catalysts. Homogeneous or heterogeneous materials containing cyclopentadienyl ligand-metal complexes that enhance the rate of olefin polymerization. Essentially single-site or dual-site. Each metal is a transition metal, alternatively Ti, Zr, or Hf. Each cyclopentadienyl ligand is independently an unsubstituted cyclopentadienyl group or a hydrocarbon-substituted cyclopentadienyl group. In some aspects, the metallocene catalyst has two cyclopentadienyl ligands, and at least one, alternatively both, cyclopentadienyl ligands are independently hydrocarbon-substituted cyclopentadienyl groups.

[0062] Oligomer content. The content of lower molecular weight polymer molecules in a copolymer, as measured by the gas chromatography method described herein.

[0063] Adjust the catalyst. A metallocene catalyst similar to a metallocene catalyst in a bimodal catalyst system. Typically, a trimmed catalyst is fed into the polymerization reactor to provide additional control over the ratio of lower molecular weight fractions to higher molecular weight fractions in the resulting bimodal copolymer.

[0064] VOC content. The content of volatile organic compounds in the copolymer, as measured by the complete evaporation method described herein.

[0065] Description of bimodal copolymers

[0066] The bimodal copolymer of the present invention is a collection of macromolecules comprising repeating units derived from ethylene monomers and repeating units derived from α-olefin comonomers having 4 to 10 carbon atoms. The comonomer may be a linear α-olefin. The comonomer may be 1-butene, 1-pentene, 1-hexene, 1-heptene, or 1-octene; alternatively, 1-butene or 1-hexene may be used, or alternatively, 1-hexene may be used.

[0067] The repeating units derived from ethylene should be at least 90% by weight, alternatively at least 95% by weight, and alternatively at least 97% by weight. The repeating units derived from ethylene should not exceed 99.95% by weight, alternatively at least 99.5% by weight, and alternatively at least 99% by weight. The repeating units derived from comonomers should be at least 0.05% by weight, alternatively at least 0.5% by weight, and alternatively at least 1% by weight. The repeating units derived from comonomers should not exceed 10% by weight, alternatively at least 5% by weight, and alternatively at least 3% by weight. Alternatively, substantially all repeating units in the copolymer are derived from ethylene or 1-hexene, meaning that the amount of repeating units derived from other monomers is small enough not to substantially alter the physical properties of the copolymer.

[0068] The copolymer may have a density of at least 0.93 g / mL, alternatively at least 0.94 g / mL, or alternatively at least 0.946 g / mL. The copolymer may have a density of at most 0.97 g / mL, alternatively at most 0.96 g / mL, or alternatively at most 0.954 g / mL.

[0069] Total average molecular weight of copolymers (M n The total molecular weight (M) of the copolymer can be at least 6000, alternatively at least 7000, or alternatively at least 7500. n The number can be up to 9000, the number of alternatives up to 8000, and the number of alternatives up to 7900.

[0070] The total weight average molecular weight (M) of the copolymer w The total weight-average molecular weight (M0) of the copolymer can be at least 250,000, alternatively at least 270,000, or alternatively at least 280,000. w It can be up to 350,000, alternatively up to 320,000, alternatively up to 300,000.

[0071] Total Z-average molecular weight of copolymers (M z The total Z-average molecular weight (M) of the copolymer can be at least 2,000,000, alternatively at least 2,500,000, or alternatively at least 3,000,000. zIt can be up to 4,500,000, alternatively up to 4,000,000, alternatively up to 3,500,000.

[0072] The total polydispersity index of the copolymer (in M) w / M n The measurement can be at least 30, alternatively at least 35, or alternatively at least 37. The total polydispersity index of the copolymer (in M...) w / M n The measurement can be up to 50, or alternatively up to 45, or alternatively up to 40.

[0073] The ratio M of the total copolymer z / M w The ratio M of the total copolymer is at least 8. z / M w It can be at least 9, and alternatively at least 10. The ratio M of the total copolymer. z / M w It can be up to 16, alternatively up to 15, alternatively up to 14.

[0074] The copolymer comprises at least 45% by weight of a higher molecular weight fraction and at least 35% by weight of a lower molecular weight fraction, wherein the weight average molecular weight (Mw) of the higher molecular weight fraction is at least 400,000 and the weight average molecular weight (Mw) of the lower molecular weight fraction is at most 50,000. The higher molecular weight fraction may alternatively comprise at least 48% by weight of the total copolymer, or alternatively at least 50% by weight, or alternatively at least 52% by weight. The higher molecular weight fraction may alternatively comprise at most 65% by weight of the total copolymer, or alternatively at most 60% by weight, and alternatively at most 55% by weight. The lower molecular weight fraction may alternatively comprise at least 40% by weight of the total copolymer, and alternatively at least 42% by weight. The lower molecular weight fraction may alternatively comprise at most 55% by weight of the total copolymer, or alternatively at most 50% by weight, and alternatively at most 48% by weight. In a preferred embodiment, the higher molecular weight fraction comprises 50% to 55% by weight of the total copolymer, and the lower molecular weight fraction comprises 40% to 45% by weight of the total copolymer. (Weight percentages are calculated only for polymer components and do not include additives, fillers, etc.).

[0075] Higher molecular weight fractions can alternatively satisfy the following molecular weight profile:

[0076] Number-average molecular weight (M) of higher molecular weight fractions n The number-average molecular weight (M) of the higher molecular weight fraction can be at least 100,000, alternatively at least 106,000, or alternatively at least 108,000. nIt can be up to 120,000, alternatively up to 115,000, alternatively up to 111,000.

[0077] The weight-average molecular weight (M) of higher molecular weight fractions w The weight-average molecular weight (M) of the higher molecular weight fraction can be at least 450,000, alternatively at least 480,000, or alternatively at least 505,000. w It can be up to 600,000, alternatively up to 550,000, alternatively up to 520,000.

[0078] The polydispersity index of higher molecular weight fractions (in terms of M) w / M n The polydispersity index (in M0.0) can be at least 3.5, or alternatively at least 4.0, or alternatively at least 4.5. The polydispersity index of higher molecular weight fractions (in M0.0) w / M n The measurement can be up to 8, or alternatively up to 6, or alternatively up to 5.

[0079] Lower molecular weight fractions can alternatively satisfy the following molecular weight spectra:

[0080] Number-average molecular weight (M) of lower molecular weight fractions n The number-average molecular weight (M) of the lower molecular weight fraction can be at least 2500, alternatively at least 3000, or alternatively at least 3500. n It can be up to 10,000, alternatively up to 6,000, alternatively up to 4,000.

[0081] Weight-average molecular weight (M) of lower molecular weight fractions w The weight-average molecular weight (M) of the lower molecular weight fraction can be at least 8,000, alternatively at least 10,000, or alternatively at least 12,000. w It can be up to 25,000, alternatively up to 16,000, alternatively up to 14,000.

[0082] The polydispersity index of lower molecular weight fractions (in M) w / M n The polydispersity index (in M0.05) can be at least 1.5, alternatively at least 2, or alternatively at least 3. The polydispersity index of lower molecular weight fractions (in M0.05) w / M n The measurement can be up to 8, or alternatively up to 6, or alternatively up to 5.

[0083] The content of repeating units derived from α-olefin comonomers in the higher molecular weight fraction can be greater than the content of repeating units derived from the same comonomers in the lower molecular weight fraction. Alternatively, the weight percentage of repeating units derived from comonomers in the higher molecular weight fraction is at least 1.1 times, alternatively at least 1.3 times, and alternatively at least 1.5 times the weight percentage of repeating units derived from comonomers in the lower molecular weight fraction. Alternatively, the weight percentage of repeating units derived from comonomers in the higher molecular weight fraction is at most 10 times, alternatively at most 5 times, and alternatively at most 3 times the weight percentage of repeating units derived from comonomers in the lower molecular weight fraction.

[0084] The oligomer content of the copolymer shall not exceed 1000 parts per million by weight (ppmw), alternatively not exceeding 750 ppmw, alternatively not exceeding 650 ppmw, and alternatively not exceeding 600 ppmw. There is no desired minimum oligomer content, but it is generally impractical to reduce the oligomer content below 100 ppmw. Low oligomer content is desirable because oligomers are prone to degradation during polymer processing, which may impair the aesthetics of the processed polymer.

[0085] The VOC content of the copolymer can be kept as low as possible under typical manufacturing conditions to reduce emissions during the manufacture of articles made from the copolymer.

[0086] Polyethylene copolymers are typically characterized based on the viscosity of the molten polymer. The melt flow ratio (I0.1) of the copolymers of this invention... 21 / I2) can alternatively be at least 90. The copolymers of the present invention can alternatively have the following melt flow characteristics:

[0087] Before and after oxygen tailoring, the flow index (I) 21 The flow rate can be at least 7 dg / min, alternatively at least 8 dg / min, or alternatively at least 8.2 dg / min. Before and after oxygen adjustment, the flow index (I0) 21 The maximum concentration can be 15 dg / min, or alternatively 12 dg / min, or alternatively 10 dg / min.

[0088] Melt flow ratio (I) before oxygen adjustment 21 / I2) (described in the following discussion of granulation) may alternatively be at least 93, or at least 96. The melt flow ratio (I) before oxygen adjustment 21 / I2) can be up to 130, alternatively up to 120, alternatively up to 110.

[0089] After oxygen adjustment, the melt flow ratio (I) 21 / I2) can be at least 105, and alternatively at least 115. The melt flow ratio (I) after oxygen adjustment 21 / I2) can be up to 170, alternatively up to 150, alternatively up to 135.

[0090] Melt flow ratio (I) 21 / I5) can be at least 20, alternatively at least 22, alternatively at least 28. Melt flow ratio (I 21 / I5) can be up to 40, alternatively up to 35, alternatively up to 32. These levels can be achieved after oxygen adjustment, even if the copolymer is at a lower level before oxygen adjustment.

[0091] Polyethylene copolymers are typically tested for a variety of physical properties related to strength, flexibility, toughness, impact resistance, and crack resistance.

[0092] The PENT value (2.4 MPa and 80°C) of the copolymers of the present invention is alternatively at least 600 (600.0) hours, indicating high crack resistance under stress. The PENT value (2.4 MPa and 80°C) is alternatively at least 800 (800.0) hours, or alternatively at least 1000 (1000.0) hours. The PENT value (3.0 MPa and 80°C) can be at least 300 (300.0) hours, or alternatively at least 500 (500.0) hours, or alternatively at least 700 (700.0) hours. There is no desired maximum PENT value, but values ​​greater than 5000 (5000.0) hours or 4000 (4000.0) hours are generally unnecessary. In some embodiments, the maximum PENT value (2.4 MPa and 80°C) is 1500 (1500.0) hours, alternatively 1400 (1400.0) hours. In some embodiments, the PENT value (2.4 MPa and 80°C) is between 1200 (1200.0) hours and 1400 (1400.0) hours. In some embodiments, the maximum PENT value (3.0 MPa and 80°C) is 1000 (1000.0) hours, alternatively 900 (900.0) hours. In some embodiments, the PENT value (3.0 MPa and 80°C) is between 600 (600.0) hours and 900 (900.0) hours.

[0093] The dart impact resistance of the copolymers of the present invention may alternatively be at least 350 g, or at least 400 g, or at least 450 g. There is no desired maximum dart impact resistance, but values ​​greater than 500 g or 600 g are generally unnecessary.

[0094] The combination of properties of the copolymers of this invention is particularly suitable for the manufacture of high stalk blown films. The polymer's melt properties make it easy to process. Its molecular weight profile makes it both robust and flexible. The low oligomer content minimizes degradation during processing.

[0095] Polymerization reactors and methods

[0096] The copolymers of the present invention are produced by polymerizing ethylene monomers and α-olefin comonomers in a reactor having a catalyst and optionally other reagents and diluents. The polymerization can be carried out in the liquid phase, slurry phase, or gas phase, but alternatively in the gas phase.

[0097] To produce a bimodal molecular weight distribution, copolymers can be generated in two-stage or one-stage polymerization, but can alternatively be prepared in one-stage polymerization.

[0098] In a two-stage polymerization, a higher molecular weight component is polymerized in a first reactor under a first set of process conditions using a first catalyst, and a lower molecular weight component is produced in a second reactor under a second set of process conditions using a second catalyst. Examples of such production are described in the following patent disclosures, which are incorporated herein by reference: US 5,627,242; US 5,665,818; US 5,677,375; US 2007 / 0043177 A1; EP-A-0 794 200; EP-B1-0 649 992; EP-A-0802 202; EP-B-634421 and WO 2009 / 148,487 A1.

[0099] In one-stage polymerization, both the higher molecular weight component and the lower molecular weight component are polymerized using a bimodal catalyst in a single reactor. Alternatively, one-stage polymerization can be carried out using a bimodal catalyst in a fluidized bed gas-phase polymerization reactor (FB-GPP reactor). Such reactors and methods are well known in the art. For example, FB-GPP reactors and methods are described in the following patent publications, which are incorporated herein by reference: US 3,709,853; US 4,003,712; US 4,011,382; US 4,302,566; US 4,543,399; US 4,882,400; US 5,352,749; US 5,541,270; US 2020 / 0024376A1, US 2020 / 024376 A1, US 2018 / 0155473 A1, and WO 2016 / 172279 A1.

[0100] The optimal operating conditions for producing the polymers of this invention vary depending on the reactor used, the catalyst system used, and the specific properties required of the copolymer. The following discussion describes the general conditions for a typical FB-GPP reactor using the following bimodal catalyst:

[0101] The molar ratio of comonomer to ethylene fed into the reactor (C) x / C2) can be at least 0.0001, alternatively at least 0.0002, alternatively at least 0.0004. The molar ratio of comonomer to ethylene fed into the reactor (C x / C2) can be up to 0.1, or alternatively up to 0.05, or alternatively up to 0.02.

[0102] The partial pressure of ethylene in the reactor can be at least 690 kPa (100 psia), alternatively at least 830 kPa (120 psia), or alternatively at least 1300 kPa (190 psia). The partial pressure of ethylene in the reactor can be at most 2070 kPa (300 psia), alternatively at most 1720 kPa (250 psia), or alternatively at most 1590 kPa (230 psia).

[0103] The molar ratio of hydrogen to ethylene (H2 / C2) in the reactor varies depending on the molecular weight of the polymer produced. The molar ratio of hydrogen to ethylene (H2 / C2) can be at least 0.0003, and alternatively at least 0.001. The molar ratio of hydrogen to ethylene (H2 / C2) can be at most 0.01, and alternatively at most about 0.006.

[0104] The catalyst system (described below) can be fed into the polymerization reactor in either a "dry mode" or a "wet mode". The dry mode consists of a dry powder or granules. The wet mode consists of a suspension in an inert liquid (such as mineral oil). Alternatively, the catalyst system can be fed in a wet mode.

[0105] Optionally, the catalyst system may comprise a main catalyst plus a "trimming catalyst" that provides additional control over the ratio of higher molecular weight components to lower molecular weight components in the final copolymer. For example, the trimming catalyst may contain a catalytic material that increases the formation of either the higher or lower molecular weight components of the copolymer. The use of trimming catalysts is described in more detail in PCT patent publications WO 2015 / 123172A1 and WO 2015 / 123179A1, which are incorporated herein by reference.

[0106] The bed temperature in the reactor can be at least 70°C, alternatively at least 80°C, or alternatively at least 85°C. The bed temperature in the reactor can be at most 110°C, alternatively at most 100°C, or alternatively at most 95°C.

[0107] Reactants can flow through the reactor at a rate sufficient to maintain the reactor bed in a fluidized state.

[0108] Optionally, an inert liquid (called an induced condensing agent or Induced Condensation Agent, ICA) can be added to the reactor to aid in cooling. The ICA can be (C5 to C5). 20 Alkanes, alternatively (C5 to C6) 10 Alkanes, alternatives to depentane or 2-methylbutane (i.e., isopentane). Uses of ICA are described in the following patent disclosures, which are incorporated herein by reference: US 4,453,399; US 4,588,790; US 4,994,534; US 5,352,749; US 5,462,999; and US 6,489,408. The concentration of ICA may be at least 1 mol%, and alternatively at least 3 mol%. The concentration of ICA may be at most 20 mol%, and alternatively at most 8 mol%.

[0109] Optionally, a continuous additive may be added to the reactor to control sheeting within the reactor. Suitable continuous additives are commercially available as CA-200 and CA-300 from Univation Technologies LLC. The concentration of the continuous additive may be at least 0.5 ppmw, and alternatively at least 30 ppmw. The concentration of the continuous additive may be up to 200 ppmw, and alternatively up to 80 ppmw.

[0110] Polymerization conditions may also include one or more additives, such as chain transfer agents or accelerators. Chain transfer agents are well known and may be alkyl metals, such as diethylzinc. Accelerators are known as in US4,988,783 and may include chloroform, CFCl3, trichloroethane, and difluorotetrachloroethane. A scavenger may be used to react with moisture before reactor start-up and during reactor transition, a scavenger may be used to react with excess activator. The scavenger may be trialkylaluminum. Gas-phase polymerization can be operated without (unintentionally added) scavengers. Polymerization conditions for gas-phase polymerization reactors / methods may also include a certain amount (e.g., 0.5 ppm to 200 ppm based on all feed entering the reactor) of electrostatic control agents and / or continuous additives, such as aluminum stearate or polyethyleneimine. Electrostatic control agents may be added to the FB-GPP reactor to suppress the formation or accumulation of static charge therein.

[0111] Start-up (cold start) of a reactivated FB-GPP reactor or restart of an FB-GPP reactor during transition (hot start) includes the period before reaching steady-state polymerization conditions. Start-up or restart may include the use of a polymer seed bed pre-loaded into the fluidized bed reactor. The polymer seed bed may consist of polyethylene powder; the polyethylene may be a bimodal copolymer similar to the bimodal copolymer intended to be prepared.

[0112] Start-up or restart of an FB-GPP reactor may also include a gas atmosphere transition, which involves purging the reactor's air or other unwanted gases with a dry (anhydrous) inert purge gas, followed by purging the FB-GPP reactor's dry inert purge gas with dry ethylene gas. The dry inert purge gas may consist essentially of molecular nitrogen (N2), argon, helium, or any mixture of two or more of these. When not in operation, the FB-GPP reactor contains an air atmosphere prior to start-up (cold start). The dry inert purge gas can be used to purge the air from a restarted FB-GPP reactor during the early stages of start-up to obtain an FB-GPP reactor with an atmosphere consisting of the dry inert purge gas. Before restart (e.g., after a seed bed change), the FB-GPP reactor in transition may contain an atmosphere of unwanted ICA or other unwanted gases or vapors. The dry inert purge gas can be used to purge unwanted vapors or gases from the FB-GPP reactor in transition during the early stages of restart to give the FB-GPP reactor an atmosphere consisting of the dry inert purge gas. Any dry, inert purge gas can be purged from the FB-GPP reactor by dry ethylene gas. The dry ethylene gas can be further contaminated with molecular hydrogen so that it is fed into the fluidized bed reactor as a mixture. Alternatively, dry molecular hydrogen can be introduced separately and after the atmosphere in the fluidized bed reactor has been converted to ethylene. The gas atmosphere conversion can occur before, during, or after heating the FB-GPP reactor to the reaction temperature for polymerization conditions.

[0113] Start-up or restart of an FB-GPP reactor also involves introducing reactants and reagents into it. Reactants include ethylene and α-olefins (e.g., 1-hexene). Reagents fed into the fluidized bed reactor include molecular hydrogen and induced condenser (ICA), as well as a bimodal catalyst system and trimmed catalyst.

[0114] Catalysts, support materials, activators

[0115] Two-reactor polymerization of bimodal copolymers can be carried out using conventional catalyst systems. Single-reactor polymerization of bimodal copolymers typically uses bimodal catalysts having one catalyst component particularly suitable for preparing the higher molecular weight (HMW) fraction of the copolymer and another catalyst component particularly suitable for preparing the lower molecular weight (LMW) fraction of the copolymer. Preferred bimodal catalyst systems preferentially direct a larger portion of the α-olefin comonomer to the higher molecular weight fraction; such bimodal catalysts (and methods for their preparation) are described in the following patent disclosures incorporated herein by reference: US 2020 / 048379 A1, US 2020 / 024376 A1, US 2018 / 0155473 A1, WO 2016 / 172279 A1.

[0116] The following describes bimodal catalyst systems particularly suitable for generating copolymers: U.S. Patent Application 62 / 880,826, entitled "Bimodal Poly(Ethylene-Co-1-Alkene) Copolymer," filed July 31, 2019; U.S. Patent Application 62 / 990,549, entitled "Metal-Ligand Complexes," filed March 17, 2020; and PCT Application PCT / US20 / 30033, entitled "Metal-Ligand Complexes," filed April 27, 2020, all of which are incorporated herein by reference.

[0117] The preferred catalyst system comprises a bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium component and a (cyclopentadienyl)(1,5-dimethylindene)zirconium (X)2 component, wherein X is the fraction that achieves the valence of zirconium. X can be a halide ion or an alkyl group containing one to four carbon atoms, and alternatively, a methyl group. Without being bound by theory, it is believed that bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium can efficiently prepare the HMW component of the bimodal copolymer, and (cyclopentadienyl)(1,5-dimethylindene)dimethylzirconium can efficiently prepare the LMW component of the bimodal copolymer.

[0118] In a bimodal catalyst system, the HMW and LMW catalysts can be kept separate until they are added to the reactor, in which case each catalyst can be unloaded or deposited on its own support. Alternatively, the HMW and LMW catalysts in the bimodal catalyst system can be deposited together on a single support.

[0119] Alternatively, the catalyst of the bimodal catalyst system can be applied to a solid support material, such as by spray drying. The support material may alternatively comprise porous inorganic or organic materials. Alternatively, the support material may comprise Group 2, 3, 4, 5, 13, or 14 metal oxides, and alternatively, Group 13 or 14 metal oxides. Examples of inorganic oxide-type support materials are silica, alumina, titanium dioxide, zirconium oxide, thorium oxide, and mixtures of any two or more of these inorganic oxides. The solid support material may alternatively be hydrophobic fumed silica (such as fumed silica treated with dimethyldichlorosilane).

[0120] The inorganic oxide support material is porous and has variable surface area, pore volume, and average particle size. In some embodiments, the surface area is 50 to 1000 square meters per gram (m²). 2 The particles are 20 to 300 micrometers (μm) in size and have an average particle size of 20 to 300 micrometers (μm). Alternatively, the pore volume is 0.5 to 6.0 cubic centimeters per gram (cm³). 3 / g), and a surface area of ​​200 to 600 m² 2 / g. Alternatively, the pore volume is 1.1 to 1.8 cm³. 3 / g, and a surface area of ​​245 to 375m² 2 / g. Alternatively, the pore volume is 2.4 cm³. 3 / g to 3.7cm 3 / g, and the surface area is 410m² 2 / g to 620m 2 / g. Alternatively, the pore volume is 0.9 cm³. 3 / g to 1.4cm 3 / g, and the surface area is 390m² 2 / g to 590m 2 / g. Each of the above properties is measured using conventional techniques known in the art.

[0121] The support material can be pretreated by heating it in air before contacting the catalyst to obtain a calcined support material. The pretreatment involves heating the support material at a peak temperature of 350°C to 850°C, alternatively 400°C to 800°C, alternatively 400°C to 700°C, or alternatively 500°C to 650°C, for a period of 2 hours to 24 hours, alternatively 4 hours to 16 hours, alternatively 8 hours to 12 hours, or alternatively 1 hour to 4 hours, thereby preparing the calcined support material. In some aspects, the support material is a calcined support material.

[0122] Alternatively, the bimodal catalyst system comprises 1.0 wt% to 5.0 wt% of bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium and 0.1 wt% to 2.0 wt% of (cyclopentadienyl)(1,5-dimethylindenyl)dimethylzirconium applied to a fumed silica support.

[0123] The trimming catalyst can be any HMW or LMW catalyst. The trimming catalyst can be the same as the HMW or LMW catalyst in the bimodal catalyst system. For the most preferred catalyst system, the trimming catalyst can be (cyclopentadienyl)(1,5-dimethylindenyl)dimethylzirconium.

[0124] For convenience, the trimmed catalyst can be fed into the reactor as a solution in a hydrocarbon solvent. The hydrocarbon solvent can be an alkane or a mixture of alkanes, wherein each alkane independently has 5 to 20 carbon atoms, or 5 to 12 carbon atoms, or 5 to 10 carbon atoms. Each alkane can be independently acyclic or cyclic. Each acyclic alkane can be independently straight-chain or branched. Examples of acyclic alkanes include pentane, 1-methylbutane (isopentane), hexane, 1-methylpentane (isohexane), heptane, 1-methylhexane (isoheptane), octane, nonane, decane, or any two or more mixtures thereof. Examples of cyclic alkanes include cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane, methylcyclopentane, methylcyclohexane, dimethylcyclopentane, or any two or more mixtures thereof.

[0125] Each catalyst in the bimodal catalyst system and the trimmed catalyst can be activated by contacting it with at least one activator. The activator may alternatively be a Lewis acid, a noncoordinate ion activator, an ionizing activator, a Lewis base, an alkylaluminoxane, or an alkylaluminoxane. The alkylaluminum may be a trialkylaluminum, an alkylaluminum halide, or an alkylaluminum alkoxide (diethylethoxyaluminum). The trialkylaluminum may be trimethylaluminum, triethylaluminum (“TEAL”), tripropylaluminum, or tri(2-methylpropyl)aluminum. The alkylaluminum halide may be diethylaluminum chloride. The alkylaluminum alkoxide may be diethylethoxyaluminum. The alkylaluminoxane may be methylaluminoxane (MAO), ethylaluminoxane, 2-methylpropylaluminoxane, or modified methylaluminoxane (MMAO). Each alkyl group in the alkylaluminum or alkylaluminoxane may be independently (C1 to C7) alkyl, alternatively (C1 to C6) alkyl, or alternatively (C1 to C4) alkyl. The molar ratio of the activator's metal (Al) to the metal (catalytic metal, such as Zr) of a specific catalyst compound can be from 1000:1 to 0.5:1, or from 300:1 to 1:1, or from 150:1 to 1:1. Suitable activators are commercially available.

[0126] Each contact step between the activator and the catalyst can be carried out independently (a) in a separate vessel outside the GPP reactor (e.g., outside the FB-GPP reactor), (b) in the feed line to the GPP reactor, and / or (c) inside the GPP reactor (in situ). In option (a), once the catalyst of the bimodal catalyst system is activated, the bimodal catalyst system can be fed into the GPP reactor in the form of a dry powder, or alternatively in the form of a slurry in a nonpolar, aprotic (hydrocarbon) solvent. In option (c), the bimodal catalyst system can be fed into the reactor through a first feed line before activation, the first activator can be fed into the reactor through a second feed line, the trimmed catalyst can be fed into the reactor through a third feed line, and the second activator can be fed into the reactor through a fourth feed line. Any two of the first to fourth feed lines can be the same or different. One or more activators can be fed into the reactor in a "wet mode" as a solution in an inert liquid such as mineral oil or toluene, in a slurry mode as a suspension, or in a dry mode as a powder. Each contact step can be carried out at the same or different times in a separate vessel, feed line, or reactor, or at different times in the same vessel, feed line, or reactor, to obtain a bimodal catalyst system and a trimmed catalyst, respectively. Alternatively, the contact steps can be carried out simultaneously in the same vessel, feed line, or reactor to obtain a mixture of the bimodal catalyst system and the trimmed catalyst in situ.

[0127] After polymerization, the preferred bimodal catalyst system typically leaves one or more dimethyl-1H-indenyl compounds as residues in the copolymer. The dimethyl-1H-indenyl compounds are reaction / decomposition products of (cyclopentadienyl)(1,5-dimethylindenyl)zirconium from the bimodal catalyst. Alternatively, the dimethyl-1H-indenyl compounds primarily comprise 3,6-dimethyl-1H-indenyl and / or 1,5-dimethyl-1H-indenyl. The copolymer may alternatively comprise at least 20 parts by weight (ppbw) of the dimethyl-1H-indenyl compound, or at least 40 ppbw, or at least 100 ppbw. Alternatively, the copolymer may alternatively comprise up to 400 parts by weight (ppbw) of the dimethyl-1H-indenyl compound, or at most 360 ppbw, or at most 200 ppbw.

[0128] Granulation and oxygen treatment

[0129] The copolymer is typically recovered from the reactor in the form of copolymer granules. Alternatively, the granules are typically converted into pellets by extrusion into filaments, which are then cut into pellets. Additives, such as stabilizers, can be added during extrusion. Furthermore, the copolymer can be “oxygen-conditioned” during extrusion by exposing it to an oxygen-containing gas, such as air, in the extruder. Extrusion with oxygen conditioning is described in US7892466B2.

[0130] membrane

[0131] Copolymer particles or granules can be formed into molded articles. A preferred molded article is a film. This film can be prepared using any extrusion or co-extrusion method, including blown film, tenter film, and cast film methods. Film extrusion equipment is commercially available, and its uses are well-known. Blown film extrusion can also be used to prepare films.

[0132] The film can be non-oriented, uniaxially oriented, or biaxially oriented. Uniaxial films can be oriented in the extrusion direction (longitudinal or MD) or in a direction transverse to the extrusion direction (transverse or TD). Biaxially oriented films can be oriented in both MD and TD by stretching or pulling in MD, simultaneously or subsequently by stretching or pulling in TD.

[0133] The resulting membrane can be a single-layer membrane, or the copolymer can be laminated as a multilayer membrane or laminate. The membrane thickness can be at least 0.0051 mm (0.200 mils), and alternatively at least 0.0077 mm (0.300 mils). The membrane thickness can be at most 0.051 mm (2 mils), alternatively at most 0.0254 mm (1.00 mils), alternatively at most 0.0203 mm (0.80 mils), and alternatively at most 0.0152 mm (0.6 mils).

[0134] Film additives may optionally be added to the copolymer during the granulation step or added in the extruder during film formation. "Film additive" is a compound or material, other than a polyolefin polymer, that imparts one or more properties to a blown film and / or enhances one or more properties of the blown film. Examples of film additives include antimicrobial agents, antioxidants, catalyst neutralizers (for unit point catalysts), colorants, and light stabilizers. Some types of blown films may alternatively comprise a bimodal copolymer, at least one antioxidant, and at least one catalyst neutralizer, and may alternatively consist essentially of these.

[0135] This film can be used to manufacture containers and packages for use in many food and non-food packaging applications. Examples of such containers are bags, such as ice packs and grocery bags. Examples of such packages are stretch films, meat wraps, and food wraps. The copolymer of this invention can also be used in a variety of non-film-related applications, including for vehicle parts.

[0136] Packaging manufacturers and consumers desire to reduce the amount of plastic in films in order to lower packaging costs and reduce the environmental impact of packaging. Improved mechanical and physical properties of films can allow for thinner films while meeting user needs. Packaging manufacturers also want to maintain easy processability and minimize oligomers in the granules they use in order to maintain optimal processability and transparency of the films they produce. The copolymers of the present invention have low oligomer content and provide easy processability, flow characteristics, and melt elasticity. When properly manufactured, the copolymers of the present invention can provide films with improved physical properties compared to similar films outside the present invention, such as improved transverse tear strength / tear resistance, puncture resistance, and / or impact resistance. Without being bound by convention, it is assumed that the improved properties are due to the molecular weight distribution of the polymer and the distribution of comonomers within the higher and lower molecular weight fractions of the copolymer.

[0137] Numbered aspects of certain embodiments of the present invention

[0138] The present invention may include any one of the following numbered aspects:

[0139] 1. A bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0140] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0141] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0142] (c) The weight-average molecular weight (M) of the higher molecular weight fraction w ) is the weight-average molecular weight (M) of the lower molecular weight fraction. w 30 to 50 times that of ).

[0143] (d) The total melt flow ratio of the copolymer (I) 21 / I2) is at least 90; and

[0144] (e) The total Mz / Mw ratio of the copolymer is at least 8; and

[0145] (f) The oligomer content of the copolymer does not exceed 1000 ppm, as measured by the gas chromatography method described herein;

[0146] 2. A bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0147] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0148] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0149] (c) The total melt flow ratio (I) of the copolymer 21 / I2) is at least 90; and

[0150] (d) The total melt flow ratio of the copolymer (I) 21 / I5) is 22 to 35; and

[0151] (e) The total Mz / Mw ratio of the copolymer is at least 8; and

[0152] (f) The oligomer content of the copolymer does not exceed 1000 ppm, as measured by the gas chromatography method described herein.

[0153] 3. A bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, based on the total weight of the copolymer, wherein:

[0154] (a) The copolymer contains at least 45% by weight of a higher molecular weight fraction, the weight-average molecular weight (Mw) of which, as measured by the gel permeation chromatography (GPC) test method described in this specification, is at least 400,000; and

[0155] (b) The copolymer comprises at least 35% by weight of a lower molecular weight fraction, the weight-average molecular weight (Mw) of which, as measured by the GPC test method, is at most 50,000; and

[0156] (c) The total melt flow ratio (Ig) of the copolymer as measured according to ASTM D1238-13 (190°C, 21.6 kg or 2.16 kg). 21 / I2) is at least 90; and

[0157] (d) The total z-average molecular weight to weight-average molecular weight (Mz / Mw) ratio of the copolymer, as measured by the GPC test method, is at least 8; and

[0158] (e) As measured by gas chromatography, based on 1,000,000 parts by weight of the copolymer, the oligomer content of the copolymer does not exceed 1,000 parts by weight (ppm); and

[0159] (f) The PENT value (2.4 MPa and 80 °C) of the copolymer is at least 600 hours, as measured by ASTM F1473-18.

[0160] 4. A bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0161] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0162] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0163] (c) The total melt flow ratio (I) of the copolymer 21 / I2) is at least 90; and

[0164] (d) The total Mz / Mw ratio of the copolymer is at least 8; and

[0165] (e) As measured by the gas chromatography method described herein, the oligomer content of the copolymer does not exceed 1000 ppm; and

[0166] (f) The copolymer is produced by polymerizing the ethylene monomer and the α-olefin comonomer in the presence of a bimodal catalyst system comprising both of the following:

[0167] (i) (cyclopentadienyl)(1,5-dimethylindenyl)zirconium (X)2 components, wherein X is the part that realizes the valence of the zirconium; and

[0168] (ii) Bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium component.

[0169] 5. A bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, wherein:

[0170] (a) The copolymer contains at least 45% by weight a higher molecular weight fraction, the higher molecular weight fraction having a weight-average molecular weight (Mi). w The number is at least 400,000; and

[0171] (b) The copolymer comprises at least 35% by weight a lower molecular weight fraction, wherein the weight-average molecular weight (Mi) of the lower molecular weight fraction is... w The maximum is 50,000; and

[0172] (c) The total melt flow ratio (I) of the copolymer 21 / I2) is at least 90; and

[0173] (d) The total Mz / Mw ratio of the copolymer is at least 8; and

[0174] (e) As measured by the gas chromatography method described herein, the oligomer content of the copolymer does not exceed 1000 ppm; and

[0175] (f) The copolymer also contains at least 20 ppb of a dimethyl-1H-indenyl compound.

[0176] 6. The bimodal copolymer according to any one of aspects 1 to 5, wherein the total melt flow ratio (I) of the copolymer is... 21 / I5) ranges from 22 to 35.

[0177] 7. The bimodal copolymer according to any one of aspects 1 to 6, wherein the PENT value (2.4 MPa and 80 °C) of the copolymer is at least 600 hours.

[0178] 8. The bimodal copolymer according to any one of aspects 1 to 7, wherein the copolymer is produced by polymerizing the ethylene monomer and the α-olefin comonomer in the presence of a bimodal catalyst system comprising both of the following:

[0179] (i) (cyclopentadienyl)(1,5-dimethylindenyl)zirconium (X)2 components, wherein X is the part that realizes the valence of the zirconium; and

[0180] ii) Bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium component.

[0181] 9. The bimodal copolymer according to any one of aspects 1 to 8, wherein the copolymer further comprises at least 20 ppb of a dimethyl-1H-indenyl compound.

[0182] 10. The bimodal copolymer according to any one of aspects 1 to 9, wherein the α-olefin comonomer is 1-hexene, and an average of 1% to 5% by weight of the repeating units in the copolymer are derived from 1-hexene.

[0183] 11. The bimodal copolymer according to any one of aspects 1 to 10, wherein the total density of the copolymer, as measured according to ASTM D792-13 (Method B), is 0.945 g / cm³. 3 ) to 0.955 g / cm 3 .

[0184] 12. The bimodal copolymer according to any one of aspects 1 to 11, wherein the higher molecular weight fraction accounts for at least 50% by weight of the copolymer, and / or wherein the higher molecular weight fraction accounts for no more than 65% by weight of the copolymer.

[0185] 13. The bimodal copolymer according to any one of aspects 1 to 12, wherein the flow index (I) is as measured according to ASTM D1238-13. 21 The concentration ranged from 8 dg / min to 12 dg / min.

[0186] 14. The bimodal copolymer according to any one of aspects 1 to 13, wherein the copolymer is formulated according to ASTM D1238-13 for I 21 The total flow ratio of the copolymer, measured by both I2 and I2 (I 21 / I2) is 100 to 150.

[0187] 15. The bimodal copolymer according to any one of aspects 1 to 14, wherein the molecular weight ratio M, as measured by the GPC test method, is... w / M n It ranges from 30 to 50.

[0188] 16. The bimodal copolymer according to any one of aspects 1 to 15, wherein the total Mz / Mw ratio of the copolymer, as measured by the GPC test method, is 9 to 15.

[0189] 17. The bimodal copolymer according to any one of aspects 1 to 16, wherein the copolymer achieves a PENT value of at least 800 hours (at 2.4 MPa) as measured according to ASTM F1473-18.

[0190] 18. The bimodal copolymer according to any one of aspects 1 to 17, wherein the copolymer achieves a PENT value of at least 1000 hours (at 2.4 MPa) as measured according to ASTM F1473-18.

[0191] 19. The bimodal copolymer according to any one of aspects 1 to 18, wherein the bimodal copolymer is prepared by polymerizing ethylene and the α-olefin comonomer in a single fluidized bed gas-phase reactor using a bimodal catalyst system.

[0192] 20. The bimodal copolymer according to aspect 19, wherein the bimodal catalyst system comprises (cyclopentadienyl)(1,5-dimethylindenyl)zirconium (X)2 component, wherein X is the portion that realizes the valence of the zirconium.

[0193] 21. A polymer formulation comprising a bimodal copolymer according to any one of aspects 1 to 20, and at least one antioxidant and at least one catalyst neutralizer.

[0194] 22. A membrane comprising a bimodal copolymer according to any one of aspects 1 to 12 or a polymer formulation according to aspect 21, the membrane having a thickness of 0.0077 mm to 0.254 mm.

[0195] 23. A method for preparing a blown film, wherein a melt of a copolymer according to any one of aspects 1 to 22 or a polymer formulation according to aspect 13 is extruded through a mold configured to form bubbles to prepare bubbles of the bimodal copolymer or the polymer formulation, and the bubbles are inflated using a blown film machine to prepare the blown film.

[0196] Example

[0197] Catalyst Synthesis

[0198] Synthesis of (cyclopentadienyl)(1,5-dimethylindenyl)dimethylzirconium. In a glove box under an anhydrous inert gas atmosphere (anhydrous nitrogen or argon), 10 mL of dimethoxyethane containing 1.000 g (6.94 mol) of 3,6-dimethyl-1H-indene was added to a 120 mL (4 oz) container. The container was then capped and its contents were frozen to -35°C. 4.3 mL of 1.6 M hexane (0.0069 mol) was added to the container, and the contents were stirred for approximately 3 hours while removing heat to maintain the contents near -35°C. Small aliquots were dissolved in d8-THF for further processing. 1The reaction progress was monitored by ¹H NMR analysis. The reaction was complete after approximately 3 hours, and the contents of the container were stirred for approximately 12 hours. When the reaction was complete, solid cyclopentadienyl zirconium trichloride (CpZrCl3) (1.821 g) was added to the contents of the container in portions while stirring. Then, methyl magnesium bromide (3.0 M in diethyl ether, 4.6 mL) was added to the contents of the container, and the contents were stirred for approximately 12 hours after the addition. The solvent was then removed under vacuum, and the product was extracted into hexane (40 mL) and filtered through diatomaceous earth, washed with another 30 mL of hexane, and then vacuum dried to provide cyclopentadienyl(1,5-dimethylindenyl)dimethylzirconium. (Cyclopentadienyl)(1,5-dimethylindenyl)dimethylzirconium was analyzed by proton NMR spectroscopy (…). 1 Confirmed by H NMR analysis. 1 ¹H NMR (C6D6): δ 7.26 (d, 1H), 6.92 (d, 1H), 6.83 (dd, 1H), 5.69 (d, 1H), 5.65 (m, 1H), 5.64 (s, 5H), 2.18 (s, 3H), 2.16 (s, 3H), -0.34 (s, 3H), -0.62 (s, 3H). This product forms the low molecular weight component of the bimodal catalyst and is a trimming catalyst.

[0199] Synthesis of bimodal catalysts. A slurry was prepared from 70.3 parts by weight of treated fumed silica (CABOSIL TS-610) in 1000 parts by weight of toluene. Subsequently, a 30 wt% solution of methylaluminoxane (MAO) in toluene, 3.54 parts by weight of bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium, and 0.229 parts by weight of (Cp)(1,5-dimethylindenyl)ZrMe2 were added. Using a spray dryer set to 160°C and with an outlet temperature of 70°C to 80°C, the mixture was introduced into the atomizing device of the spray dryer to generate droplets. The mixture was then contacted with a hot nitrogen stream to evaporate the liquid from the mixture, yielding a powder. The powder was separated from the gas mixture in a cyclone separator and discharged into a container to obtain a catalyst as a fine powder. The resulting powder was made into a slurry to obtain an activator formulation containing 22% solids in 10% isoparaffinic fluid and 68% mineral oil.

[0200] Synthesis and testing of particulate copolymers

[0201] Ethylene and 1-hexene are copolymerized in a fluidized bed gas-phase polymerization reactor (“FB-GPP reactor”), which has a reaction zone inner diameter of 304.8 mm (12 inches) and a straight-side height of 2.4384 m (8 ft) and contains a bimodal fluidized bed of ethylene-co-1-hexene copolymer particles. The FB-GPP reactor has a circulating gas line for facilitating the circulation of the circulating gas. This circulating gas line has a gas feed inlet and a polymer product outlet.

[0202] Three different runs were conducted to produce the copolymer, named IE1, IE2, and Comparison A. Runs IE1 and IE2 are embodiments of the present invention. Comparison A is a comparative example. Before each run, the reactor was purged with anhydrous nitrogen and brought to the temperature and pressure shown in Table 1. Then, ethylene, hexene, hydrogen, bimodal catalyst, trimming catalyst, induced condensate, and continuous additives were fed into the reactor in the amounts and conditions shown in Table 1.

[0203] Table 1: Operating conditions for IE1, IE2, and Comparison A .

[0204]

[0205]

[0206] The particulate copolymer from the reactor was continuously discharged into a discharge tank, which was purged with nitrogen for 10 to 30 seconds before being poured into fiber packaging, and then purged with a mixture of nitrogen and moisture for 3 hours. The properties of the particulate copolymer were measured using the test methods described at the end of these examples. The results are reported in Table 2 below.

[0207] Table 2: Copolymer Properties .

[0208] <![CDATA[QC density (g / cm 3 )]]> 0.951 0.951 0.951 <![CDATA[Melt flow index, I 21 (dg / min)]]> 9.5 7.9 9.7 <![CDATA[MFR2,I 21 / I2]]> 100 110 94 <![CDATA[MFR5,I 21 / I5]]> 26.1 26.9 25.7

[0209] Granulation and properties

[0210] A portion of each type of granular resin was extruded in a laboratory-scale extruder to form pellets without oxygen adjustment. The pellet properties shown in Table 3 below were measured from the pellets using the test methods described below.

[0211] Table 3 .

[0212]

[0213]

[0214] N / m was not measured.

[0215] Using the oxygen (O2) levels adjusted in Table 4, a portion of the particulate copolymer from IE1 was mixed in a belt mixer with 800 parts by weight (ppm) of antioxidant 1, 200 ppm of antioxidant 2, 1,000 ppm of catalyst neutralizer 1, and 500 ppm of catalyst neutralizer 2, respectively, according to the methods described in US 5,728,335 and US 6,989,423, and then compounded into wire-cut pellets using a twin-screw extruder LCM100. The properties of the resulting copolymer were measured and reported in Table 4 below.

[0216] Antioxidants: 1. Pentaerythritol tetra(3-(3,5-bis(1',1'-dimethylethyl)-4-hydroxyphenyl)propionate; available from BASF in the form of IRGANOX 1010. 2. Tris(2,4-bis(1',1'-dimethylethyl)-phenyl)phosphite; available from BASF in the form of IRGANOX 168.

[0217] Catalyst neutralizers: 1. Calcium stearate. 2. Zinc stearate.

[0218] Table 4: Melt Properties

[0219] <![CDATA[O2 adjustment level (%)]]> 7 <![CDATA[density (g / cm 3 )]]> 0.950 <![CDATA[I 21 (190℃,21.6kg)(day / min)]]> 8.5 <![CDATA[MFR5(I 21 / I5)]]> 30.2 <![CDATA[MFR2(I 21 / I2)]]> 120

[0220] Film formation process :

[0221] Using an Alpine 50 mm barrier single-screw extruder with a length-to-diameter (L / D) ratio of 25:1, a 120 mm inner diameter die, and a 1.2 mm die gap, copolymer granules were extruded separately and blown into films without IBC (internal bubble cooling). Film characteristics were measured for a thickness of 0.0127 mm = 12.7 μm. See Table 5 below. Example IE1 of this invention exhibits higher dart drop and puncture resistance than Comparative Example A, while maintaining similar tear strength and fracture stress.

[0222] Table 5: Membrane properties .

[0223] Melt elasticity (G' / G” at 0.1 radians / second) 0.631 0.624 Dart (g) 482 401 Tear strength, MD(g) 19.5 20.5 Tear strength, TD(g) 65.8 47.6 Fracture stress, MD (MPa) 50.4 49.3 Fracture stress, TD (MPa) 41.5 33.8 <![CDATA[Puncture resistance, J / cm 3 > 6.50 5.25

[0224] Table 6: Test Methods

[0225]

[0226] molecular weight

[0227] Molecular weight, including peak molecular weight (M), was measured using conventional gel permeation chromatography (GPC). p(GPC)), weight-average molecular weight (M w(GPC) Number-average molecular weight (M) n(GPC) ) and z-average molecular weight (M z(GPC) ), and report in grams per mole (g / mol).

[0228] The chromatographic system was a PolymerChar GPC-IR (Valencia, Spain) high-temperature GPC chromatograph equipped with an internal IR5 infrared detector. The autosampler chamber was set to 160°C and the column chamber to 150°C. Four Agilent "Mixed A" 30 cm x 20 μm linear mixed-bed columns were used. The chromatographic solvent was 1,2,4-trichlorobenzene containing 200 parts per million (ppm) of butylated hydroxytoluene (BHT). The solvent source was nitrogen bubbling. The injection volume was 200 μL, and the flow rate was 1.0 mL / min.

[0229] The column was calibrated using at least 20 narrow molecular weight distribution polystyrene standards ranging from 580 g / mol to 8,400,000 g / mol. The standards were arranged in a mixture of six “liquids” with each molecular weight spaced at least ten times apart. These standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000 g / mol, standards were prepared at a rate of 0.025 g per 50 mL of solvent, and for molecular weights less than 1,000,000 g / mol, standards were prepared at a rate of 0.05 g per 50 mL of solvent. The standards were dissolved by gentle stirring at 80 °C for 30 minutes. The standard peak molecular weights were converted to ethylene-based polymer molecular weights using Equation 1 (as described in Williams and Ward, *Journal of Polymer Science: Polymer Letters*, 6, 621 (1968)).

[0230] M 聚乙烯 =A×(M) 聚乙烯 ) B Equation 1

[0231] Where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.

[0232] A fifth-order polynomial was used to fit the corresponding ethylene-based polymer-equivalent calibration point. (In the examples, a small adjustment to A (from approximately 0.39 to 0.44) was required to correct for column resolution and band broadening effects, resulting in the NIST standard NBS 1475 with a molecular weight of 52,000 g / mol.)

[0233] Total plate counts were performed on the column using eicosane (prepared in 50 mL of TCB at a dose of 0.04 g and dissolved under gentle stirring for 20 minutes). Plate counts were measured with a 200 μL injection (Equation 2) and symmetry (Equation 3) according to the following equations:

[0234]

[0235] Where RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the peak maximum height, and half the height is half the peak maximum height.

[0236]

[0237] Where RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, one-tenth height is one-tenth of the height of the peak maximum, a subsequent peak refers to the tail of the peak at a retention volume later than the peak maximum, and a preceding peak refers to the front of the peak at a retention volume earlier than the peak maximum. The plate count of the chromatographic system should be greater than 22,000, and the symmetry should be between 0.98 and 1.22.

[0238] Samples were prepared semi-automatically using PolymerChar "Instrument Control" software, with a target sample concentration of 2 mg / mL. A solvent containing 200 ppm BHT was added to a pre-bubbled, septum-capped vial via a PolymerChar high-temperature autosampler. The sample was dissolved by shaking at 160°C on low speed for 3 hours.

[0239] Based on the GPC results obtained using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph according to Equations 4 to 7, the PolymerChar GPCOne was used. TM Software, at each equally spaced data collection point i (IR) i The IR chromatogram at point i (M) minus the baseline and the result from point i (M) according to Equation 1 聚乙烯,i The M-value was determined by using a narrow standard calibration curve (in g / mol) to obtain the polymer equivalent molecular weight based on ethylene. n(GPC) M w(GPC) and M z(GPC) The calculation is then performed. Subsequently, a GPC molecular weight distribution (GPC-MWD) plot (wt.) of the ethylene-based polymer sample can be obtained. GPC (lgMW)) Compare the plot of lgMW, where wt GPC(lgMW) is the weight fraction of ethylene-based polymer molecules with a molecular weight of lgMW. Molecular weight (MW) is expressed in g / mol, wt. GPC (lgMW) follows Equation 4.

[0240] ∫wt GPC (lgMW)dlgMW=1.00 Equation 4

[0241] M n(GPC) M w(GPC) and M z(GPC) Calculate using the following equation:

[0242]

[0243]

[0244]

[0245] M p(GPC) On GPC-MWD plotting wt GPC (lgMW) represents the molecular weight at its highest value.

[0246] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by a PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (nominal flow rate) for each sample by comparing the RV (RV(FM sample)) of the corresponding decane peak within the sample with the RV (RV(FM calibrated)) of the decane peak within the narrow standard calibration. It was then assumed that any variation in the decane marker peak time was linearly related to the flow rate (effective flow rate) throughout the run. To achieve the highest accuracy in measuring the RV of the flow marker peak, a least-squares fitting procedure was used to fit the peak values ​​of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated according to Equation 11. Processing of the flow marker peak was performed via PolymerCharGPCOne. TM The software is complete. Acceptable flow rate correction ensures that the effective flow rate is within 0.5% of the nominal flow rate.

[0247] Flow rate 有效 =flow rate 标称 ×(RV(FM 校准 ) / RV(FM 样品 Equation 8

[0248] Bimodality test method:GPC chromatograms containing the local maximum log(MW) values ​​of the LMW and HMW polyethylene component peaks are obtained by plotting dWf / dLogM (mass detector response) on the y-axis against LogM on the x-axis. The presence or absence of local minima between the LMW and HMW polyethylene component peaks is then observed to determine the presence or absence of resolved bimodality. dWf represents the change in weight fraction, dLogM (also called dLog(MW)) represents the logarithmic change in molecular weight, and LogM (also called Log(MW)) represents the logarithm of molecular weight.

[0249] Deconvolution test method: The chromatogram obtained using the bimodal test method is divided into nine (9) Schulz-Flory molecular weight distributions. Such deconvolution methods are described in US 6,534,604. The four lowest MW distributions are assigned to the LMW polyethylene component and the five highest MW distributions are assigned to the HMW polyethylene component. By mathematical processing of the known aggregated Schulz-Flory MW distributions, the weight fractions (Wf) of the LMW and HMW polyethylene components are used, along with the corresponding number-average molecular weights (M). n ), weight-average molecular weight (M w ) and z-average molecular weight (M z The sum of the values ​​determines the corresponding weight percentage (wt%) of each of the LMW and HMW polyethylene components in the bimodal ethylene-co-1-hexene copolymer.

[0250] Total VOC content was determined by the complete evaporation method. .

[0251] Volatile organic compounds (VOCs) in polyethylene were determined using headspace gas chromatography with a flame ionization detector. One natural resin pellet (0.04 ± 0.02 g) and 0.005 g of Irganox 1330 were placed in a headspace vial and sealed. VOCs were sampled using a headspace analyzer, where the sample was equilibrated at 190 °C for 120 min. A calibration solution was prepared using the process solvent in dichloromethane. 10 μL aliquots of the calibration solution were transferred to headspace vials using an electronic digital injector, and the vials were immediately sealed with a cap using a crimping tool. The peak areas of the solvent peaks in the sample and calibration solution were summed. Quantification was performed using an external standard calibration procedure. Data are reported in parts per million (ppm; μg / g).

[0252] The total oligomer content was determined by gas chromatography.

[0253] Weigh approximately 5 g of sample (and record to the nearest 0.0001 g) into a 120 mL (4 oz) glass vial, followed by the addition of 20 mL of dichloromethane. Seal the vial with a PTFE-lined cap. Extract the sample for 24 hours at room temperature using a wrist shaker. Transfer an aliquot of the extract to a 2 mL glass autosampler vial using a glass pipette. Cap the vial and place it on a gas chromatograph for analysis. Analyze the sample extract, dichloromethane blank, and certified reference standards (Ultra Scientific, C10 to C44, even hydrocarbons, 200 parts per million (ppm) of n-decane, n-tetradecane, and n-trisane, and all other components in hexane at 100 ppm) using a chromatographic data system. 44 H 90 The peak areas of all peaks eluted between samples were calculated. Peak areas of additives such as Irgafos 168, oxidized I-168, and Irganox 1076 were excluded using settings in the chromatographic data system. An external standard calibration procedure was used, calculated from the total peak area of ​​oligomer peaks in the sample and the peak areas of 100 ppm n-eicosane (C1076) in the calibration standard. 20 H 42 The peak area is used to calculate the parts per million (ppm) of oligomers. Data on oligomers in resins are reported in ppm; μg / g.

Claims

1. A membrane comprising a bimodal copolymer, said bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, based on the total weight of said copolymer, said membrane having a thickness of 0.0077 mm to 0.254 mm, wherein: (a) The copolymer comprises at least 45% by weight of a higher molecular weight fraction, the weight-average molecular weight (Mw) of which, as measured by gel permeation chromatography (GPC), is at least 400,000; and (b) The copolymer comprises at least 35% by weight of a lower molecular weight fraction, wherein the weight-average molecular weight (Mw) of the lower molecular weight fraction, as measured by the GPC test method, is at most 50,000; and (c) The weight-average molecular weight M of the higher molecular weight fraction w The weight-average molecular weight M of the lower molecular weight fraction w 30 to 50 times; and (d) The total melt flow ratio I of the copolymer, as measured according to ASTM D1238-13 at 190°C, at 21.6 kg or 2.16 kg. 21 / I2 is between 100 and 150; and (e) The total z-average molecular weight / weight-average molecular weight Mz / Mw ratio of the copolymer, as measured by the GPC test method, is at least 8; and (f) As measured by gas chromatography, based on 1,000,000 parts by weight of the copolymer, the oligomer content of the copolymer does not exceed 1,000 parts by weight (ppm).

2. The membrane according to claim 1, wherein the total melt flow ratio of the bimodal copolymer is I 21 / I5 is 22 to 35.

3. The membrane according to claim 1 or 2, wherein the PENT value of the bimodal copolymer, measured at 2.4 MPa and 80°C, is at least 600 hours.

4. The membrane according to claim 1 or 2, wherein the bimodal copolymer is produced by polymerizing the ethylene monomer and the α-olefin comonomer in the presence of a bimodal catalyst system comprising both of the following: (i) (cyclopentadienyl)(1,5-dimethylindenyl)zirconium (X)2 component, wherein X is the portion that realizes the valence of said zirconium; and ii) Bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium component.

5. The membrane according to claim 1 or 2, wherein the bimodal copolymer further comprises at least 20 ppb of a dimethyl-1H-indenyl compound.

6. The membrane according to claim 1 or 2, wherein the α-olefin comonomer is 1-hexene, and an average of 1% to 5% by weight of the repeating units in the bimodal copolymer is derived from 1-hexene.

7. The membrane according to claim 1 or 2, wherein the total density of the bimodal copolymer, as measured according to ASTM D792-13, Method B, is 0.945 g / cm³. 3 Up to 0.955 g / cm 3 .

8. The membrane according to claim 1 or 2, wherein the higher molecular weight fraction comprises 50% to 65% by weight of the bimodal copolymer.

9. The membrane according to claim 1 or 2, wherein the flow index I of the bimodal copolymer, as measured according to ASTM D1238-13, is... 21 The concentration ranged from 8 dg / min to 12 dg / min.

10. The membrane according to claim 1 or 2, wherein the bimodal copolymer is oxygen-adjusted by exposure to oxygen-containing gas in an extruder, and conforms to ASTM D1238-13 for I 21 The total flow ratio I of the bimodal copolymer, as measured by both I2 and I2. 21 / I2 is at most 130 before oxygen adjustment or at least 105 after oxygen adjustment.

11. The membrane according to claim 1 or 2, wherein the molecular weight ratio M of the bimodal copolymer, as measured by the GPC test method, is... w / M n It ranges from 30 to 50.

12. The membrane according to claim 1 or 2, wherein the bimodal copolymer achieves a PENT value of at least 1000 hours at 2.4 MPa, as measured according to ASTM F1473-18.

13. The membrane according to claim 1 or 2, wherein the bimodal copolymer is prepared by polymerizing ethylene and the α-olefin comonomer in a single fluidized bed gas-phase reactor using a bimodal catalyst system.

14. The membrane according to claim 1 or 2, further comprising at least one antioxidant and at least one catalyst neutralizer.

15. A method for preparing a film according to any one of claims 1-14, wherein the film is a blown film, the method comprising extruding a melt of the bimodal copolymer through a mold configured to form bubbles to prepare bubbles of the bimodal copolymer, and inflating the bubbles with a blown film machine to prepare the blown film.

16. A bimodal copolymer comprising, on average, at least 90% by weight of units derived from ethylene monomers and at least 0.05% by weight of units derived from α-olefin comonomers having 4 to 10 carbon atoms, based on the total weight of the copolymer, wherein: (a) The copolymer comprises at least 45% by weight of a higher molecular weight fraction, the weight-average molecular weight (Mw) of which, as measured by gel permeation chromatography (GPC), is at least 400,000; and (b) The copolymer comprises at least 35% by weight of a lower molecular weight fraction, wherein the weight-average molecular weight (Mw) of the lower molecular weight fraction, as measured by the GPC test method, is at most 50,000; and (c) The weight-average molecular weight M of the higher molecular weight fraction w The weight-average molecular weight M of the lower molecular weight fraction w 30 to 50 times; and (d) The total melt flow ratio I of the copolymer, as measured according to ASTM D1238-13 at 190°C, at 21.6 kg or 2.16 kg. 21 / I2 is between 100 and 150; and (e) The total z-average molecular weight / weight-average molecular weight Mz / Mw ratio of the copolymer, as measured by the GPC test method, is at least 8; and (f) As measured by gas chromatography, based on 1,000,000 parts by weight of the copolymer, the oligomer content of the copolymer does not exceed 1,000 parts by weight (ppm). The bimodal copolymer is produced by polymerizing the ethylene monomer and the α-olefin comonomer in the presence of a bimodal catalyst system, the bimodal catalyst system comprising both of the following: (i) (cyclopentadienyl)(1,5-dimethylindenyl)zirconium (X)2 component, wherein X is the portion that realizes the valence of said zirconium; and ii) Bis(2-(pentamethylphenylamino)ethyl)amine dibenzylzirconium component.

Citation Information

Patent Citations

  • Process for gas phase polymerization of olefin

    EP0634421A1

  • Staged reactor polymerisation process

    EP0794200A2

  • Fluidized bed polymerization reactor

    EP0802202A1

  • Internal bubble cooling control system and method

    US20020150648A1

  • Polymer composition and process to manufacture high molecular weight-high density polyethylene and film therefrom

    US20070043177A1